Sosialisasi Bahaya Internet Bagi Remaja dan Pengaturan Hukumnya di SMPN Satu Atap Desa Padang Mutung Kabupaten Kampar - Deliana, Evi; Asrori, Taufik; Pasaribu, Venaldy Tesalonika; Barus, Yeji Akkai Fadillah; Surbakti, Dinda Rejekinta BR; Syarah, May; Rizki, Malla Diah; Julaikha, Siti; Nurbaiti, Nurbaiti; Sapitri, Nadya; Debora, Indi Listia (Unri Conference Series: Community Engagement, 2025)
A socialization about the dangers of internet use and legal protection for junior high school students at SMPN Satu Atap Padang Mutung was conducted to improve digital literacy and understanding of digital law among participants. This activity used interactive lectures, discussions, and case simulations to explain the benefits and risks of the internet, such as cyberbullying, hoaxes, online fraud, pornography, and personal data protection, accompanied by an explanation of the provisions of the latest ITE Law. This socialization activity aims to provide knowledge and information to teenagers so they can be careful when using the internet. The community service was conducted by socialization to junior high school students at SMPN Satu, Atap Padang Mutung Village. Before the socialization, only a few students were aware of the dangers of the internet and the regulations in force in Indonesia regarding legal violations that utilize the internet as a medium. After socialization, the number of students who knew about the dangers and legal regulations related to the internet increased. With the socialization, it was found that participants showed interest and active involvement in the socialization process, with an increased understanding of internet risks and the legal consequences they might face. The socialization results show that students' knowledge of the dangers of the internet is growing. It is hoped that with knowledge and understanding of the risks of the internet and legal regulations related to violations in cyberspace, students will not commit acts that violate the law and will be able to protect themselves and their environment from the dangers of using the internet that do not comply with the rules.